Galectin-3 Mediated Inflammatory Response Contributes to Neurological Recovery by QiShenYiQi in Subacute Stroke Model - Wang, Yule; He, Shuang; Liu, Xinyan; Li, Zhixiong; Zhu, Lin; Xiao, Guangxu; Du, Xiaoli; Du, Hongxia; Zhang, Wen; Zhang, Yiqian; Orgah, John; Feng, Yuxin; et al. (Frontiers in Pharmacology, 2021)
Effective therapies for stroke are still limited due to its complex pathological manifestations. QiShenYiQi (QSYQ), a component-based Chinese medicine capable of reducing organ injury caused by ischemia/reperfusion, may offer an alternative option for stroke treatment and post-stroke recovery. Recently, we reported a beneficial effect of QSYQ for acute stroke via modulation of neuroinflammatory response. However, if QSYQ plays a role in subacute stroke remain unknown. The pharmacological action of QSYQ was investigated in experimental stroke rats which underwent 90 min ischemia and 8 days reperfusion in this study. Neurological and locomotive deficits, cerebral infarction, brain edema, and BBB integrity were assessed. TMT-based quantitative proteomics were performed to identify differentially expressed proteins following QSYQ treatment. Immunohistochemistry, western blot analysis, RT-qPCR, and ELISA were used to validate the proteomics data and to reveal the action mechanisms. Therapeutically, treatment with QSYQ (600 mg/kg) for 7 days significantly improved neurological recovery, attenuated infarct volume and brain edema, and alleviated BBB breakdown in the stroke rats. Bioinformatics analysis indicated that protein galectin-3 and its mediated inflammatory response was closely related to the beneficial effect of QSYQ. Specially, QSYQ (600 mg/kg) markedly downregulated the mRNA and protein expression levels of galectin-3, TNF-α and IL-6 in CI/RI brain as well as serum levels of TNF-α and IL-6. Overall, our findings showed that the effective action of QSYQ against subacute phase of CI/RI partly via regulating galectin-3 mediated inflammatory reaction.